Pengaruh Liberalisasi Ekonomi Terhadap Ketimpangan Pendapatan Di Indonesia - Ratna Christianingrum (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This study aims to determine the impact of economic liberalization on income inequality in Indonesia. This study used sectoral FDI as an indicator of financial liberalization and net export as an indicator of trade liberalization. We also used the employment rate as an intermediate indicator. We used panel regression to analyze data. This study shows that sectoral FDI has a significant and positive effect on the employment rate in the primary and tertiary sectors. But in the secondary sector, sectoral FDI has a significant and negative effect on the employment rate, because of the SBTC phenome. Financial liberalization has an indirect effect on income inequality in Indonesia because the sectoral employment rate has a significant effect on income inequality. Trade liberalization also has a significant effect on income inequality.